Construction Of Heritage Rights and Citizenship Status Differences in Indonesia - Subagiyo, Dwi Tatak (Universitas Wijaya Kusuma Surabaya, 2021)
The high mobility of the population from one country to another, contributes to citizenship transfer. Likewise, Indonesian Citizens (WNI) who, for reasons of education, employment, and other preferences, choose to become Foreign Citizens (foreigners). However, the transfer of citizenship does not necessarily eliminate the ties of blood with the family. For example, in Inheritance in the form of land, a Foreign Citizen, referred to as a WNA, can inherit land rights in Indonesia due to the first two things, a foreign citizen born because of a mixed marriage. And both foreign citizens as a result of naturalization can be understood as a change in the citizenship status of the Indonesian population. Therefore, Indonesia's current construction of inheritance rights within the framework of inheritance regulation (which is part of civil law) is still dualistic and pluralistic. This is inseparable from the legal history of the enactment of civil law in Indonesia.Keywords: Construction, Inheritance, Citizenship